Equipment and Separation Units for Flow Chemistry Applications and Process Development. Issue 10 (21st June 2019) - Bittorf, Lukas; Reichmann, Felix; Schmalenberg, Mira; Soboll, Sebastian; Kockmann, Norbert
Abstract: Process development and small‐scale production gets more and more important in fine chemistry and pharmaceutical production. An equipment toolbox assists process synthesis presented in this contribution. A microfluidic calorimeter can measure kinetic and thermodynamic reaction data with commercial plate reactors. A tubular reactor coiled with 90° bends allows for long residence time with low axial dispersion, also known as coiled flow inverter (CFI). A similar setup is used for continuous‐flow cooling crystallization. Small‐scale columns with rotating internals are employed for distillation and liquid‐liquid extraction. Main emphasis will be put on automation and scale‐up in future steps. Abstract : An equipment toolbox with microcalorimeters, capillary coiled flow inverters, and separation columns assists process synthesis in the laboratory. A set of miniaturized equipment allowing for implementing entire continuous chemical processes on laboratory scale is introduced. Appropriate design rules are provided with hints for successful equipment manufacturing and operation.